Social and political challenges of the Digital Single Market and of increasing connectivity: digital literacy and network power - Silva, Elsa Costa e (UNIO – EU Law Journal, 2018)
This article seeks to reflect on the construction of a Digital Single Market (DSM) and on initiatives aimed at increasing the connectivity of European citizens. The widespread access to internet has obvious advantages for citizens and businesses, but it also gives rise to challenges for society. There are two principal issues. Firstly, digital literacy and the power of the players. First, the benefits of the availability of a particular technology do not just result from widespread access. They result, to a large extent, from the capacity of people to take advantage of the use and from the practices that are promoted. Thus, policies to promote technology cannot be dissociated from policies to promote media and digital literacy. Secondly, generalizing access to the Internet can further enhance the power of the players who, at this moment, already concentrate a large part of Internet users’ activity. This issue concerns matters of economic competition, but also of social power to provide symbolic frameworks to read the world.